Complications of sickle cell anaemia in children in Northwestern Tanzania. Issue 4 (20th April 2016) - Saidi, Hamza; Smart, Luke R.; Kamugisha, Erasmus; Ambrose, Emmanuela E.; Soka, Deogratias; Peck, Robert N.; Makani, Julie
Abstract : Objectives : Tanzania has the third highest birth rate of sickle cell anaemia (SCA) in Africa, but few studies describe severity of complications or available treatments, especially in Northwest Tanzania around Lake Victoria where the sickle gene is most prevalent. This is a report of the spectrum of clinical disease and range of interventions available at Bugando Medical Centre (Bugando) in Northwest Tanzania in Africa. Methods : A cross-sectional study was carried out in Bugando between 1 August 2012 and 30 September 2012. Children (<15 years old) with SCA attending Bugando were sequentially enrolled. A trained research assistant completed a Swahili questionnaire with the parent or guardian of each participant concerning demographic information, clinical features of disease, and treatments received. Results : Among the 124 participants enrolled, the median age was 6 years (interquartile range [IQR] 4–8.5), and only 13 (10.5%) were < 3 years old. Almost all participants (97.6%) had a prior history of a vaso-occlusive episode, 83 (66.9%) had prior acute chest syndrome, and 21 (16.9%) had prior stroke. In the preceding 12 months, 120 (96.8%) had been hospitalized, and a vaso-occlusive episode was the most common reason for hospitalization (35.5%). Prescriptions for folic acid (92.7%) and malaria prophylaxis (84.7%) were common, but only one had received a pneumococcal vaccine, and none had received hydroxyurea or prophylactic penicillin. Conclusion : Children with SCA receiving care in Tanzania are diagnosed late, hospitalized frequently, and have severe complications. Opportunities exist to improve care through wider access to screening and diagnosis as well as better coordination of comprehensive care.